2015
DOI: 10.1007/s12571-015-0509-y
|View full text |Cite|
|
Sign up to set email alerts
|

Observations of entomophagy across Benin – practices and potentials

Abstract: Food security is a critical issue for many lowincome countries, particularly in Sub-Saharan Africa. Appropriately identifying and utilising local resources can provide sustainable solutions to food security problems. Insects, which are traditionally consumed in many regions of the world, represent one such resource. Insects can be nutritionally rich and therefore could be used to address issues of malnutrition. A first step towards utilising insects as a resource is identifying which ones are traditionally con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 20 publications
2
42
1
Order By: Relevance
“…The significant (but small) differences in percentage of respondents consuming insects in urban and rural areas can be an indication that entomophagy is not declining in either urban or rural areas in Zimbabwe, as suggested by other authors for other countries (Obopile and Seeletso 2013;Riggi et al 2016). Likewise, the expectation that due to increased migration from rural to urban areas the consumption of traditional foods (under which edible insects are classified) would be abandoned, was not confirmed.…”
Section: Insect Consumption Patternsmentioning
confidence: 74%
See 4 more Smart Citations
“…The significant (but small) differences in percentage of respondents consuming insects in urban and rural areas can be an indication that entomophagy is not declining in either urban or rural areas in Zimbabwe, as suggested by other authors for other countries (Obopile and Seeletso 2013;Riggi et al 2016). Likewise, the expectation that due to increased migration from rural to urban areas the consumption of traditional foods (under which edible insects are classified) would be abandoned, was not confirmed.…”
Section: Insect Consumption Patternsmentioning
confidence: 74%
“…Differences in preferences and prevalence of consumption of specific species have also been attributed to availability (Niaba et al 2012;Obopile and Seeletso 2013;van van Huis 2013), ethnicity (Chakravorty et al 2011;Obopile and Seeletso 2013;Riggi et al 2016), palatability ) and seasonality (Kinyuru et al Kinyuru et al 2013). Hanboonsong et al (2013) reported different insect eating habits due to availability of different species in different regions.…”
Section: Insect Consumption Patternsmentioning
confidence: 99%
See 3 more Smart Citations